Psychosocial safety climate (PSC) at middle management level in the healthcare sector: A contribution to the Italian validation of psychosocial safety climate-4 - Fattori, Alice; Comotti, Anna; Bordini, Lorenzo; Dollard, Maureen F.; Bonzini, Matteo (Frontiers in Psychology, 2022)
Psychosocial safety climate (PSC) refers to workers’ shared perceptions of organizational policies, practices and procedures for the protection of psychological health and safety. PSC offers a multilevel organizational approach that expands traditional models of workplace stress, giving a more comprehensive understanding of occupational health and safety issues. Although considerable research on psychosocial risks in the healthcare sector has been conducted, few studies have explored the role of PSC among healthcare workers at middle management level. Additionally, no validated version of PSC is available in Italian language. The aim of this study is to contribute to the validation of the Italian 4-item version of the PSC and to explore this theory within the Job Demands-Resources model (JD-R) among a sample of Italian healthcare workers by testing PSC at the middle management level. We used cross-sectional data from 276 employees working in 17 different wards in a large Italian hospital. Intra-class coefficient (ICC) coefficient and agreement index were used to test PSC as a climate construct (data nested to hospital ward level). We performed hierarchical linear models to test mediation and moderation effects. The Italian version of PSC-4 proved to have good psychometric properties and confirmed its role as a group-level construct (α=0.84; ICC=0.16). Multilevel random coefficient models showed PSC was associated with Job Demands (Effort: B=-0.36, SE=0.07; Emotional Demands: B=-0.03, SE=0.01) and Job Resources (Reward: B=1.16, SE=0.01; Physical work environment: B=0.06, SE=0.01). Results confirmed the indirect effect of PSC on Psychological (Burnout) and Occupational Health (Job Satisfaction) outcomes supporting the role of Job Resources and Job Demands as mediators. The multilevel analysis did not find a significant interaction terms between PSC and Job Demands on Burnout therefore the moderation hypothesis was not supported. The Italian version of PSC-4 is a valid tool to evaluate PSC. These findings sustain the multilevel framework of PSC and the significant role played by mid-leaders in both the health impairment and motivational path. Further studies should explore the buffering effect of PSC at higher baseline levels as well as the adoption of PSC as a target for occupational health intervention the Italian context.